2017
DOI: 10.1371/journal.pone.0179887
|View full text |Cite
|
Sign up to set email alerts
|

Clinimetric properties of hip abduction strength measurements obtained using a handheld dynamometer in individuals with a lower extremity amputation

Abstract: IntroductionSuitable handheld dynamometer (HHD)-techniques to test hip abduction strength in individuals with a lower extremity amputation, irrespective of their amputation level are absent. The aim of this study was to optimise a HHD-technique and to test its reproducibility and validity.MethodsThis study involved three phases, in which two techniques were evaluated. Both HHD-techniques used a lever-arm of 22 centimetre. HHD-technique 1 used a break-technique. After obtaining within-session test-retest reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…These findings are generally in line with the literature, e.g. hip joint muscles strength deficit in people with TFA of up to 35% when compared to unimpaired peers [7,10,41].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are generally in line with the literature, e.g. hip joint muscles strength deficit in people with TFA of up to 35% when compared to unimpaired peers [7,10,41].…”
Section: Discussionsupporting
confidence: 91%
“…Some further musculoskeletal comorbidities following lower-limb amputation are: low back pain, osteoarthritis, reduced bone density and volume loss and atrophy of involved muscles [1]. These changes related to muscle function lead to a deficit in muscle strength, as reported in previous studies investigating individuals with a transtibial amputation (TTA) [2][3][4][5][6][7][8] and transfemoral amputation (TFA) [5,7,[9][10][11][12]. Although the impact on muscle function is obvious, it remains unclear how the deficit in strength relates to function and, more specifically, to walking.…”
Section: Introductionmentioning
confidence: 99%
“…Leijendekkers et al, 16 conducted a study with amputees, which one of the objectives was to test the intra-examiner reliability and the validity of the use of portable dynamometer, with and without external stabilization. The result was a good reliability, especially when the techniques were applied with stabilizers during the test.…”
Section: Discussionmentioning
confidence: 99%
“…The study that evaluated the intra-examiner reliability of amputees observed the measurements of strength of hip movements, considering the remaining movements depending on the level of amputation. 16 Changes are expected on the amputated side, such as strength loss and atrophy or hypotrophy; however, the last two can occur not only in the amputated side, but also globally. 17 Since unilateral amputation leads to changes in gait kinematics, the monitoring of strength gain in the preserved limb is essential in the process of prosthesis adaptation, reinforcing the need to evaluate the remaining limb to plan for the balance recovery, confidence for movement, and gait.…”
Section: Introductionmentioning
confidence: 99%
“…In future studies, other variables such as pain catastrophizing (the tendency to ruminate and exaggerate pain situations), depression, and quality of life should be considered as outcomes of avoidance behavior 8 . In addition, although manual muscle testing has been validated for use in individuals with an amputation, 31 others have deemed it challenging to exert the correct amount of force to counter the participants' muscle action 32 . However, to increase the reliability for the measurements, one rater performed all study measures.…”
Section: Study Limitationsmentioning
confidence: 99%